THE PEATLAND RESTORATION AGENCY’S ECONOMIC REVITALIZATION PROGRAM IN ACHIEVING THE TRANSBOUNDARY HAZE-FREE ASEAN 2020 IN RIAU PROVINCE - Yusnarida Eka Nizmi; Yessi Olivia; Umi Oktyari Retnaningsih; M Saeri; Ahmad Jama’an; Alfajri Alfajri (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
This study analyses the implementation of good governance principles for the economic revitalization program under the supervision of Riau Province’s Badan Restorasi Gambut (Peatland Restoration Agency). One of the aims of this program is to support the haze-free ASEAN 2020 roadmap. Riau province is an area prone to forest fire disasters. Its peatland area, which is larger than Malaysia’s total peatlands, have a very high potential for damage due to forest fires. To mitigate the damages, BRG initiated the 3R program: Rewetting, Revegetation, and Revitalization. What makes this topic interesting is BRG emphasizes the aspects of economic empowerment of local communities to prevent further forest and peatland damages. To assess the implementation of BRG’s program, our research team conducted several interviews with representatives from Indonesia’s Ministry of Environment and Forestry, NGOs, academics, farmers, and villages’ facilitators who assisted local communities that received the BRG’s assistance packages. Our study shows that BRG’s economic revitalization program had succeeded in creating small scale economic activities such as honey industry, pineapple farming, and catfish farming. However, the ineffective coordination and communication between BRG and the local communities had prevented them from constructing an effective method to prevent future forest fires.